HISTORICAL AND THEORETICAL FOUNDATIONS OF THE SCIENCE OF LINGUISTICS - Adilova Soliyakhon (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
Nowadays, the economic, cultural and scientific relations between the nations have been further strengthened. Thus, the connections show that language is interrelated with culture and language. Already in the 20th century, scientists who study culture and language realized that these areas can be the basis of a new science. This field was named by them linguistic and cultural studies. That is, a new science in modern linguistics that combines language and culture.